ANALISIS DIGITAL MARKETING UNTUK PENINGKATAN PENJUALAN PRODUK : ANALISIS STRATEGI DAN IMPLEMENTASI EFEKTIF - Kisworo, Yudo (Journal of Information System, Applied, Management, Accounting and Research, 2024)
This study evaluates the effectiveness of digital marketing in increasing product sales and brand equity, especially for MSMEs, with a focus on platforms such as Facebook, Instagram, WhatsApp, GoFood, and GrabFood. With internet penetration in Indonesia reaching 79.5%, the importance of digital marketing in influencing purchasing decisions is getting greater. The purpose of the study is to assess the influence of digital platforms, integrated marketing strategies (SEO, content marketing, social media, paid advertising), as well as their impact on business growth and entrepreneurs' skills. The methods used include qualitative and qualitative analysis of ten previous studies. The results show that digital platforms and integrated marketing strategies significantly increase sales and brand equity. However, the study also identified limitations such as sample coverage and the impact of the pandemic. Recommendations for future research include sample expansion, platform diversification, and adoption of quantitative methods to gain more comprehensive insights.